Marketing Operational in Increasing the Level of Occupancy at Century Park Hotel Jakarta - Septi Fahmi Choirisa; Adestya Ayu Armeilia (Universitas Multimedia Nusantara, 2018)
AbstractOccupancy is one measure of the success of a hotel in the competition for market share. Such a large target is a challenge for the sales and marketing team in designing strategies for meeting the targets. There are more than 20 four star hotels located in Central Jakarta that are fighting for market share in order to meet hotel occupancy targets. One of them is Hotel Century Park Jakarta is a four star hotel located in Central Jakarta which has a target of high occupancy rate every day.With several new hotels growing rapidly today, Hotel Century Park Jakarta’s sales and marketing team is required to have specific strategies to gain market share. This study aims to find out what operational strategies conducted by the sales and marketing team in increasing the occupancy rate of the Hotel Century Park Jakarta. The research method used is descriptive qualitative research that describes some of the strategies used from the year 2013-2016. Interviewed teh key informant and took some data analysis of occupancy rate of Occupancy Hotel Century Park Jakarta.There are three strategies used by the Jakarta Century Park sales & marketing team, Fortress defense as a strategy to maintain its market, Market Expansion as a strategy to expand its market share and Gerilya Strategy as a step in acquiring competitor market share as the main target. Based on the research result, Hotel Century Park Jakarta is able to compete with several four-star hotels in Jakarta and become the vanguard in the occupancy competition from 2013-2016.Keywords: Marketing Operational Strategy, Hotel Century Park Jakarta, Occupancy